INTERNATIONAL SEMINAR OF STUDENTS IN SPECIAL EDUCATION AND REHABILITATION "ZLATIBOR 2013" (Journal of Special Education and Rehabilitation, 2014)
Organized by the Student Parliament of Faculty of Special Education and Rehabilitation, Belgrade, the Seminar of Students of Special Education and  Rehabilitation "Zlatibor 2013" was held from November 20th to 24th. Parallel to this seminar, there was a seminar organized by the Students Parliament of MajeureMedical School, Belgrade. Enveloped in the beauty of Zlatibor, housed in the student resort "Ratko Mitrovic", this congress was attended by 287 students from the Balkans, of which 146 were students of special education and rehabilitation, 17 of them were from Macedonia, 14 from Bosnia and  Herzegovina, 12 from Croatia, 6 from Slovenia and the rest were from Serbia. Officially, the seminar was opened by the President of the Student Parliament of Faculty of Special Education and Rehabilitation, Belgrade Nikola Nicin. After his introductory address, the speech was led by Prof. Vladimir Trajkovski, PhD.The students’ presentations were organized throughout three days in morning sessions and afternoon sessions. Institute for Special Education and Rehabilitation of Macedonia was represented by six undergraduate students and one postgraduate student. On November 20th, Lazar Trifunovic and Voislav Dosev presented a topic: Attitudes of Primary School Teachers from "Dane Krapchev" in Skopje, on inclusion of students with special needs. During the same day, the afternoon session was opened by Krchanoska Manuela, who spoke on topic Access in Public Libraries for Persons with Disabilities in Macedonia, and afterwards Ana Kostadinovska and Gordana Blagojevska presented the topic Analysis of the Pshyhological Base of American and Macedonian Sign Language. On the same day, Ema Donevska presented the topic: Reactions of the Parents at the First Announcement of the Developmental Disabilities of Their Child. On the second day, morning session was opened by Marija Dimovska’s presentation on the topic: Inclusion of Children with Autistic Spectrum Disorders in the Regular Pre-school Institutions in Skopje. Many papers written by students in special education and rehabilitation on various topics were presented there, which effected on increasing of knowledge and competence in future educators. The Seminar was enriched with the presentation held by Christina Davidovic, PhD and Marko Pavlovic that was entitled “Presentation Skills”. On the next day, the same subject was held as a workshop, which was really successful. Lastly, to make the impression even stronger, there was a presentation of Prof. Milenko Kundachina, PhD, who talked of academic writing. In an hour and half as the course of his lecture, Professor Kundachina explained how to write a scientific paper. Seminar was officially closed by the speech of the President of the Student Parliament of Faculty of Rehabilitation and Special education in Belgrade Nikola Nicin, president  of the Student Parliament of Majeure Medical School, Savo Papic, Prof.Vladimir Trajkovski, PhD and representatives from each country. After their closing speeches all participants were awarded with certificates. Organisational board of this congress hopes that this congress is just the beginning and that organizing congresses of this kind will become a tradition.